2013
DOI: 10.1056/nejmoa1301675
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk among Children Born after Assisted Conception

Abstract: There was no increase in the overall risk of cancer among British children born after assisted conception during the 17-year study period. Increased risks of hepatoblastoma and rhabdomyosarcoma were detected, but the absolute risks were small. (Funded by Cancer Research UK and others.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
117
5
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(141 citation statements)
references
References 35 publications
14
117
5
4
Order By: Relevance
“…Moreover, neither parental age nor ART seems to be associated with an increased cancer risk in our study cohort. This is in line with previous findings that children born after ART are not at increased cancer risk [15,17].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, neither parental age nor ART seems to be associated with an increased cancer risk in our study cohort. This is in line with previous findings that children born after ART are not at increased cancer risk [15,17].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, an increased risk of hepatoblastoma has been detected in children born after assisted conception or presumed use of infertility treatment. 42,43 However, for these children as well, the risk seems to be associated with low birth weight and not with assisted conception. 43,44 The premature birth rates increase worldwide including the majority of industrial countries such as Germany.…”
Section: -2004mentioning
confidence: 99%
“…42,43 However, for these children as well, the risk seems to be associated with low birth weight and not with assisted conception. 43,44 The premature birth rates increase worldwide including the majority of industrial countries such as Germany. 45 It has been suggested that the improved survival of preterm babies might explain the increasing trend of hepatoblastomas and that some factors in neonatal intensive care could contribute to it.…”
Section: -2004mentioning
confidence: 99%
“…A few previous published studies reported positive associations between CL, infertility [8,9] and some fertility treatments [8,[10][11][12], albeit with inconsistency regarding the type of treatment. Petridou et al [12], reported a twofold increase in risk with in vitro fertilization (IVF), but the finding was not replicated by Rudant et al [8] in the ESCALE study or in a recent UK cohort study [13]. On the contrary, the ESCALE study showed an association between CL and ovulation induction without IVF or artificial insemination (AI), suggesting a role of drugs other than gonadotropins.…”
Section: Introductionmentioning
confidence: 98%